Ecospiritualism in Buddhist Communities and Its Contribution to Sustainable Development - Dewi Kusumasanthi; Ida Kade Suparta; I Made Sudarma; I Nyoman Alit Suarjaya (Center for Research and Publication (PUSLITPEN), UIN Syarif Hidayatullah Jakarta, 2026)
This research originates from the increasing environmental degradation on Lombok Island and studies of ecospiritualism within Buddhist communities in Dusun Tebango and Jeliman Ireng as an alternative solution based on local wisdom. It aims to analyze the concept of ecospiritualism, its transmission, and the implications of ecospiritual values on community life, and their implementation in sustainable development. The study adopts a qualitative method with an ethnographic approach, utilizing semi-structured interviews, non-participant observation, and documentation, which are analyzed using the Miles and Huberman model. The results indicate that the community understands ecospiritualism as the sacredness of nature that is in harmony with humanity and the spiritual dimension. These values are transmitted orally and through religious practices and traditions, thus forming the collective experience of the community. In the context of sustainable development, ecospiritualism serves as a moral foundation that shapes social and cultural behavior and environmental awareness, as reflected in efforts at natural conservation, respect for the sources of life, and the maintenance of local traditions that preserve the balance between humans and nature. These research findings indicate that ecospiritualism functions as an important foundation for sustainable development rooted in local wisdom.